AB0677 Late onset systemic lupus erythematosus: Is it actually a milder variant?. (23rd January 2014) - Ovalles-Bonilla, J.G.; Martínez-Barrio, J.; Lόpez-Longo, F.; de la Torre, I.; González, C.; Valor, L.; Montoro-Άlvarez, M.; Aramburu, F.; Marín, C.; Martínez-Estupiñán, L.; Nieto, J.; Hinojosa, M.; et al.
Abstract : Objectives: To describe the clinical and immunological features, the damage accrual and mortality of late onset compared with adult onset SLE. Methods: The data was obtained from a long term prospective cohort of 353 patients diagnosed with SLE in the Rheumatology Department of Gregorio Marañon Hospital in Madrid, Spain. Demographic, clinical, and laboratory data were collected at disease onset and during it's course from 1986 to 2006. Patients were divided into 2 groups: adult onset 19-49 years (n=276) and late onset ≥50 years (n=77). Organ damage was scored using the Systemic Lupus International Collaborative Clinics/American College of Rheumatology (SLICC/ACR) Damage Index. Results: A total of 353 patients were recruited, with a following mean time of 11 years. The female to male ratio differed significantly (p=0.005) between groups. At diagnosis, the late-onset group presented cutaneous manifestations less frequently (p<0.001). During follow-up, the late-onset group presented a lower incidence of arthritis (p=0.02), malar rash (p=0.001), photosensitivity (p=0.04), fever (p=0.03), low serum complement (p=0.001), hematologic (p=0.03) and renal (p=0.01) manifestations. The late-onset group had significantly more hypertension (p=0.03), neoplasms (p=0.02), damage accrual (p=0.007) and mortality (p=0.006). As for autoantibody profile, no statistically significant differences were found. Conclusions: Late onset SLE is clinically different with less arthritis, fever, low serum complement, cutaneous, hematologic and renal manifestations compared with the adult onset group. The higher frequency of damage accrual, mortality and hypertension observed in the late-onset group can be affected by aging-related factors other than disease activity or duration. Disclosure of Interest: None Declared